Point Frame Measurements of Moss and Vascular Frequencies Under Increasing N Deposition Over Five Years, 2011-2015 - R Kelman Wieder; Dale H Vitt; Melanie A Vile; Jeremy A Graham; Jeremy A Hartsock; Hope Fillingim; Melissa House; James C Quinn; Kimberli D Scott; Meaghan Petix; Kelly J McMillen (Environmental Data Initiative, 2019)
Development of the oil sands has led to increasing atmospheric N deposition, with values as high as 17 kg N ha -1 yr -1 ; regional background levels <2 kg N ha -1 yr -1 . Bogs, being ombrotrophic, may be especially susceptible to increasing N deposition. To examine responses to N deposition, over five years, we experimentally applied N (as NH 4 NO 3 ) to a bog near Mariana Lakes, Alberta, at rates of 0, 5, 10, 15, 20, and 25 kg N ha -1 yr -1 , plus controls (no water or N addition). Anchored point frames were established at each plot and measure at 30 points along the frame each year in July. We used absolute frequencies of Sphagna and vascular plants to examine species and community responses to N treatment. Increasing N input led to decreased frequency of S. fuscum in the third through fifth year of N addition (Fig. 10A) and an increased frequency of S. magellanicum in the second through fifth year of N addition Dominant shrubs, all shrubs, and all vascular plant species frequencies generally increased with increasing N input, with those increases all significant in 2013-2015 (Fig. 10 G-I). Water addition alone had no significant effect on the frequency of vascular plant species or groups in any of the five years (p >= 0.12). At Mariana Lakes Bog, we observed changes in vegetation even at low experimental N loadings, with vegetation progressively changing over the 5 years of the study (Figs. 10,11). These results suggest that bogs that have persisted under very low ambient N deposition may be especially sensitive to increasing N deposition, in terms of plant species relative abundances and plant community composition.